Legal Analysis of Diversion Efforts on Criminal Acts of Sexual Violence by Children as Perpetrators - Andre Prakoso; Adianto Mardijono (Syntax Corporation Indonesia, 2023)
This paper aims to explain diversion efforts in sexual violence crimes committed by children. Knowing the weaknesses of diversion efforts if these efforts are applied in sexual violence crimes committed by children. This paper uses a normative juridical method with a statutory approach as well as a conceptual approach with two legal materials, namely the law on criminal acts of sexual violence, the law on child protection and the law on the juvenile justice system. The result of this study is that the crime of sexual violence is a crime against the sexuality and dignity of another person's body. The perpetrators of this crime are not only adults but also children who will later be referred to as children in conflict with the law. The perpetrator's child has a different justice system as stated in the spa law with its specialty, namely diversion efforts. However, this does not support the goal of diversion itself which prioritizes the interests of the victim and provides a deterrent effect on children as perpetrators. It is said that diversion efforts will be enforced if the sentence is under 7 years, whereas there are articles that provide sentences under 7 years. The conclusion of this study is that the diversion effort does not fulfill the objective value of the diversion itself and can result in a loss of deterrent effect on the perpetrator so that the interests of the victim are not prioritized.